Penerapan Teknologi Operasional Penggunaan Mesin Pencuci Telur Asin Bagi UKM ‘Mak Ngat’ Desa Purwerejo Kec. Suruh Kab. Semarang - Trio Setiyawan; Riles WM; Suharto Suharto; Sugeng Irianto; Nurhidayati Nurhidayati; Hery Tristijanto; Avicenna An-Nizhami (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Survey results from several salted egg manufacturing businesses where in the process of cleaning eggs from the mud mixture using tools in the form of fibers or wires so that the remaining mud stuck to it can be cleaned. Craftsmen who are experienced enough can only clean around 150 eggs or around 12 kg in one hour, of course this is less efficient if the production scale of the UMKM is large. The partners for this community service activity are UMKM which are engaged in making salted eggs. one of the problems faced is in the process of washing salted eggs, which is a process that is carried out before being marketed, where the process still uses manual washing power using human power, manual washing requires less efficient time so that when there are orders, many UMKM experience problems. to fulfill orders from consumers. UMKM that operate in the egg business sector really need a touch of technology related to the salted egg washing method. With this problem, in Community Service Activities for UMKM, salted egg washing machines will be handed over to partner entrepreneurs, namely UMKM Mak Ngat, Purworejo Village, Suruh District, Semarang Regency. The impact of using a salted egg washing machine on Mak'Ngat UMKM is that the salted egg washing process is more economical, namely when done manually it can clean around 150 eggs or around 12 kg in one hour, but when done using a machine the cleaning capacity reaches 45 kg per hour and this number rose drastically.